Baker’s Strategies Used in Translating English Idioms Into Indonesian in Crazy Rich Asians By Kevin Kwan - Fitri, Okta Maya; Faridi, Abdurrachman; Hartono, Rudi (Universitas Negeri Semarang, 2019)
The use of appropriate strategies to translate idioms determines the quality of the idiom translation because the meaning of idioms cannot be extracted from its each component word. The research was conducted to describe the types of idioms found in Crazy Rich Asians novel and to analyze the strategies used in translating the idioms by applying Baker’s translation strategy. The data were taken from idioms found in Crazy Rich Asians novel. There were 325 data which were analyzed qualitatively to determine the types of idioms and what strategies were employed. The use of appropriate strategies to translate idioms determines the quality of the idiom translation because the meaning of idioms cannot be extracted from its each component word.The research was conducted to describe the types of idioms found in Crazy Rich Asians novel and to analyze the strategies used in translating the idioms by applying Baker’s translation strategy.The data were taken from idioms found in Crazy Rich Asians novel. There were 325 data which were analyzed qualitatively to determine the types of idioms and what strategies were employed. The result shows that opaque phrases dominated of all idiom types, followed by semi-transparent phrase, semi-opaque phrase and transparent expression. There were five strategies employed in translating idioms, they were using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, translation by paraphrase, translation by omission and literal translation. Translation by paraphrase is the most frequent strategies used to translate idioms because the equivalent idioms in Bahasa Indonesia are not available. Even though in Baker’s strategy does not include literal translation, this strategy is applicable to translate transparent expression, but it is not appropriate in translating opaque phrases. This research will be beneficial as the source of information and reference related to the translation of idioms.